Reduction of muscle injuries and improved post-exercise recovery by branched-chain amino acid supplementation: A systematic review and meta-analysis - Rahimlou, M.; Ramezani, A.; Mahdipour, M.; Palimi, E.; Moradipoodeh, B. (Journal of Nutrition Fasting and Health, 2020)
This meta-analysis and systematic review aimed to attain specific data on the effect of branched-chain amino acids (BCAAs) administration on muscle injuries and the indices of delayed-onset muscle soreness (DOMS) after exercise. Literature search was performed in databases such as Scopus, ISI, Web of Science, Scientific Information Database (SID), Cochrane Controlled Register of Trials (CENTRAL), and Cochrane library for the articles published until January 2017. The clinical trials examining the effects ofBCAA administration on athletes were considered eligible. In total, 42 studies were evaluated in terms of eligibility, 26 of which were excluded from the meta-analysis. According to the meta-analysis, BCAA supplementation significantly reduced the levels of creatine kinase 24 hours post-exercise (mean difference: -129.55 [95% CI: -237.02--22.07] IU/l; P=0.018). However, BCAA administration could not decrease lactate dehydrogenase promptly (mean difference: -10.11 [95% CI: -21.76-1.53] IU/l; P=0.08) 24 hours post-exercise (mean difference: -14.66 [95% CI: -32.16-2.83] IU/l; P=0.10). Therefore, it could be concluded that BCAA consumption is inversely associated with DOMS at 24 hours (standardized mean difference [SMD] =-0.43 [95% CI: -0.71--0.16]; P=0.002), 48 hours (SMD=-0.55 [95% CI: -0.81--0.29]; P<0.0001), and 72 hours post-exercise (SMD=-0.44 [95% CI: -0.72--0.16]; P=0.002). Furthermore, the findings of the systematic review and meta-analysis indicated that BCAA supplementation could alleviate muscle damage within the first 24 hours after exercise, and it seems that the consumption of daily doses of BCAA is more effective in the recovery of athletes compared to the periodic doses.